A NEW PLIOCENE SPERM WHALE FROM VIGLIANO D’ASTI, PIEDMONT, NORTHWEST ITALY - Bisconti, Michelangelo; DANIELLO, RICCARDO; STECCA, RICCARDO; CARNEVALE, GIORGIO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
A new sperm whale species is described from the late Zanclean (Early Pliocene) of Piedmont, northwest Italy, based on a partial vertebral column and parts of the forelimb. The new taxon, Eophyseter damarcoi gen. nov. sp. nov., is characterized by elongated vertebral centra in the thoracic and lumbar regions of the vertebral column, wider and higher articular facets for the occipital condyles in the atlas, elliptical and dorsoventrally compressed posterior articular facet of the axis-bearing block, ulna with posteriorly convex margin. These characters distinguish Eophyseter damarcoi gen. nov. sp. nov.from other physeteroids and show that the vertebral proportions are differently arranged with respect to those of the extant sperm whale species. A phylogenetic analysis was performed to understand the relationships of Eophyseter damarcoi gen. nov. sp. nov. by adding 20 postcranial characters to a previous character x taxon matrix; it revealed that E. damarcoi gen. nov. sp. nov. forms a clade with P. macrocephalus. A taphonomic analysis suggested that the carcass of the holotype specimen of Eophyseter damarcoi gen. nov. sp. nov. was exploited by sharks and colonized by barnacles and molluscs; however, a quick burial prevented its total destruction by other invertebrates, as usual in the cetacean fossil record from the Pliocene of Piedmont.